“DE NOVO” PERIAORTITIS AFTER EVAR OR AORTOILIAC STENTING: A SYSTEMATIC REVIEW - Mendes, Daniel (2021)
Chronic periaortitis and retroperitoneal fibrosis are related entities that develop with periaortic inflammation and deposition of fibroinflammatory tissue in the retroperitoneal space. This pathological fibroinflammatory process may be associated with endovascular treatment of abdominal aortic aneurysms (EVAR) as well as the treatment of aortoiliac arterial occlusive disease with stent/stent-graft implantation. We performed a systematic review of the literature in the MEDLINE database of original articles that documented the development of periaortitis after endovascular aortoiliac treatment for occlusive and aneurysmatic arterial disease. We included a total of 12 articles describing 14 cases of this complication. Most of the reported cases are related to the development of periaortitis after EVAR in the treatment of abdominal aortic aneurysms (AAA). The majority of patients are male, with ages ranging from 45 to 78 years. This complication was verified with the use of different devices that included nitinol or stainless-steel stents. In the case of stent-grafts this complication occurred with both polyester and polytetrafluoroethylene (PTFE) coverings. The severity of the clinical picture was also highly variable, with some cases presenting with hydronephrosis resulting from urethral obstruction. Treatment with corticotherapy, tamoxifen, or a combination of the two was effective in all cases. Periaortitis is an extremely rare complication of aortoiliac endovascular treatment. Similar to idiopathic retroperitoneal fibrosis, corticosteroid therapy appears to be highly effective and early treatment seems to be essential to avoid complications.